A Systematic Review : Interactive Media in Mathematics learning, What do we get? - Purnama, Roni; Farmansyah, Daffa; Yuniarti, Erni; Aminah, Neneng; Asnawati, Sri (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The use of learning media is now essential for the success of learning. Developments in learning media continue to be carried out today to produce interactive media that requires students to interact with teachers, friends, and learning media. This is common in mathematics learning. This research aims to find data regarding the learning media that are most frequently used in the world, the countries that use interactive learning media the most in mathematics learning, and the mathematics materials that are most widely used in using interactive learning media. The method used is a systematic review using the PRISMA method. From the initial results, there were 381,837 articles, which were then filtered according to predetermined criteria, and the final results were 8 articles for further research. The results of this research found that Interactive Media is widely used in mathematics lessons throughout the world such as Digital Books, Geogebra, Geometer's Sketchpad, ChatGPT, and Instructional Video. Of the various interactive media, digital books are the ones most used in learning because digital books can stimulate the skills needed for learning in the 21st century. The results of this research also found that Ethiopia and Germany are the most users of interactive media. Geometry material is material that is considered difficult so it is most widely used in interactive media in various countries.